Current Legal Issues Affecting Central Banks, Volume V - Effros, Robert (Washington, D.C. : International Monetary Fund, 1998)
This volume, edited by Robert C. Effros, focuses on how technology is affecting the world of banking and finance in an era of increasing globalization. The advent of electronic money, stored value cards, and internet transactions are discussed, as well as the impact of technology on cross-border banking and its implications for central banks. Other issues examined are the legal and regulatory frameworks for risk management of banks, sovereign debt, the international laws of bank secrecy, and financial services within the context of the GATT Agreement on Trade Services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet